Dietary fats and immune status in athletes: clinical implications - Venkatraman, J. T.; Leddy, J.; Pendergast, D. (Medicine & Science in Sports & Exercise, 2000)
Athletes are competitive, train at very high levels with inadequate rest, consume too few calories, avoid fats, and may be at increased risk of infections. The immune system is sensitive to both fat intake and intense exercise, suggesting that athletes may have suppressed immune function. It has been reported that many athletes consume about 25% fewer calories than the estimated expenditure, leading to low intakes of some essential micronutrients and fats. Acute exercise has been shown to increase inflammatory and decrease antiinflammatory immune factors and may increase oxidant stress. Chronic exercise appears to improve immune competence. Lipids are powerful mediators of the immune system, and they may modulate the immunosuppressive effects of strenuous exercise. Studies have shown that a low-fat high-carbohydrate diet (15% fat, 65% CHO, 20% protein of total calories), typically eaten by athletes, increases inflammatory and decreases antiinflammatory immune factors, depresses antioxidants, and negatively affects blood lipoprotein ratios. Increasing total caloric intake by 25% to match energy expenditure and the dietary fat intake to 32% in athletes appears to reverse the negative effects on immune function and lipoprotein levels reported on a low-fat diet. Increasing the dietary fat intake of athletes to 42%, while maintaining caloric intake equal to expenditure, does not negatively affect immune competency or blood lipoproteins, whereas it improves endurance exercise performance at 60-80% of V(dot)O2max in cyclists, soldiers, and runners. There is no evidence that higher fat intakes (up to 42% of total calories), in calorically balanced diets, increase the risk of cancer, but studies are needed to determine whether the beneficial effects of higher fat diets in athletes reduce their rate of infections.